VP22 Applying The IDEAL Framework To NICE Interventional Procedure Guidance. (2019) - Anjum, Sharika; Powell, John; Harris, Kevin
Abstract : Introduction: The IDEAL (Idea, Development, Exploration, Assessment, Learning) Framework measures the maturity of evidence base behind surgical innovation. The NICE Interventional Procedures (IP) programme issues guidance for the United Kingdom National Health Service (NHS) on use of surgical innovation. One of four recommendations can be made: (a) standard arrangements, (b) special arrangements, (c) research only, and (d) do not use. This study aimed to investigate whether the recommendation of NICE IP guidance corresponded with the stage of innovation as determined by IDEAL, thus IDEAL's role in informing future guidance production. Methods: A retrospective sample of 103 pieces of guidance issued between 2015 and 2018 was analysed. One researcher examined the evidence base and determined the corresponding stage of the IDEAL framework, numbered 1, 2, 2a, 3 and 4. The primary outcome measure was the association between stage of evidence on IDEAL framework and the recommendation of published NICE IP guidance. Results: There were twenty-one (20 percent), thirty-three (32 percent), three (3 percent), forty (39 percent) and six (6 percent) procedures at IDEAL stages 1, 2, 2a, 3 and 4, respectively. Of those at stage 1 (idea), 48 percent were given research only arrangements, 43 percent special arrangements, and 10 percent standard. Many of the procedures at stages 2 (development) and 2a (exploration) were given standard arrangements (39 percent and 67 percent respectively). Forty-three percent of stage 3 (assessment) and 67 percent of stage 4 (learning) guidance were identified standard. At stage 4 none were given a 'research only' recommendation. Conclusions: Procedures given 'standard' arrangements guidance are more likely have a mature and robust evidence base as determined by IDEAL. Those with limited evidence are more likely to be given a more cautious 'research only' guidance. Routine use of this framework could help inform future guidance production however cannot replace the decision-making function of the NICE committee which also involves patient experiences, population characteristics, risk of serious safety events, and equity issues.